Gas chromatography - mass spectrometry (GC-MS) based metabolic fingerprinting of three Malaysia ginger (zingiber officinale rosc.) cultivars - Budi Muljono, Julia Retno Andayani; Ishak, Mahdi (2010)
A comprehensive metabolic fingerprinting of three micro propagated ginger explants, Bukit Tinggi, Tanjung Sepat and Sabah cultivars, was carried out using Gas chromatography coupled with mass spectrometry (GC-MS). The ginger leave tissues were fractionated in a polar (MeOH) and non polar (CHCl3) solvents, subsequently methoximated and silylated prior to GC-MS analysis. By applying this technique, over 300 metabolites (polar and non-polar) in total were detected in each ginger cultivar. However, only about 25% of these compounds can be definitely characterised by using the Wiley7n.1 and the NIST Mass spectra libraries for the best hit of the molecular ion peaks and the fragmentation patterns. Fatty acids and sugars (mono− and disaccharides) as the main constituents of the ginger leaf tissues besides a small amount of essential amino acids as well as some organic acids. In addition, a distinct GCMS metabolic fingerprinting in each of the ginger cultivar can be used as “unequivocal pattern recognition” among the ginger phenotype derived from Bukit Tinggi, Tanjung Sepat and Sabah.